Comprehensible Input Production of Second Language Learner Through Informal Form-Focused Instruction - Putu Ngurah Rusmawan (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2017)
This research aims to describe basic concept of Form-Focused Instruction (FFI) and try to explain further that the use of FFI in producing comprehensible input for second language learner. The interactional process can be obtained from SLL (second language learner) while doing the assignment in narrative reading text. The teacher let them discus the assignment about narrative text reading. The students are going to contribute knowledge, discuss, and give the correction each other. This study uses descriptive qualitative in nature because in this research describes and shows several type of FFI which is used by the students. The researcher tries to use an audio recorder to obtain voices of students’ interaction. To be more specific, the audio recorder tool refers to cell phone recorder. The researcher will analyze the conversation then interpret based on FFI theory The FFI will not be treated by the teacher but the advance students will give the corrective feedback because in discussion the teacher just plays role as facilitator and the teacher may not interrupt and intervene to the students’ discussion. In this research, the students can interact well. Their interaction produces negotiate meaning, recast, and feedback that construct comprehensible input. In this study, the researcher classifies the students’ interaction pattern SLL interaction based on those three components of interaction. The students to interact, share, learn, and contribute knowledge each other. Therefore, it produces comprehensible input from the interaction